Studies on forced degradation and solid state stability of tenofovir disoproxil orotate - Nageswara Rao Jakkam; Sudhakar Chintakula; Sreenivasa Rao Battula (International Journal of Research in Pharmaceutical Sciences, 2021)
In order to develop a stability regulatory system for drug substances and degraded products, a forced degradation study is an essential part in the design of the method. As per ICH Guidelines Q1A in 1993, it was established as an essential requirement for the regulatory system to assess the stability of drugs and their degradation products under the degradation studies by force. These analytical methods are helpful in the development of stability, indicating the method by conducting the studies on forced degradation with their mechanism of degradation. Drug products by degradation and new drug substance by forced degradation conditions are more severe than a demonstration of specificity of stability indicating methods. The analytical method development is facilitated by those techniques for better understanding of (API) active pharmaceutical ingredients and (DP) drug products stability.